2005
DOI: 10.1002/art.21239
|View full text |Cite
|
Sign up to set email alerts
|

The presence of molecular markers of in vivo lipid peroxidation in osteoarthritic cartilage: A pathogenic role in osteoarthritis

Abstract: Objective. To investigate the role of oxidative functions in human osteoarthritic (OA) chondrocytes and to investigate the presence of in vivo molecular markers of lipoxidation in OA cartilage.Methods. An in vitro model of cartilage collagen degradation was used. Lipid peroxidation activity and overall oxidative function in OA chondrocytes were monitored by cis-parinaric acid and dichlorofluorescein assays, respectively. In vivo molecular markers of lipoxidation in normal and OA cartilage were studied using im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 43 publications
3
42
0
1
Order By: Relevance
“…11 In particular, malondialdehyde (MDA), a toxic 12 Shah et al also showed that chondrocyte derived lipid peroxidation mediates collagen degradation. 1 In the present study, erythrocyte MDA levels were significantly high (p<0.05 & p<0.001) in study group subjects, which clarify the role of lipid peroxidation in knee OA progression and development of CVD risk. Oxidation of lipids is well controlled by antioxidant enzymes including plasma paraoxonase, an enzyme found in association with HDL contributing it to anti-atherogenic and antioxidant capability by hydrolyzing specific oxidized phospholipids and cholesterol linoleate hydroperoxides, and by neutralizing hydrogen peroxide.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…11 In particular, malondialdehyde (MDA), a toxic 12 Shah et al also showed that chondrocyte derived lipid peroxidation mediates collagen degradation. 1 In the present study, erythrocyte MDA levels were significantly high (p<0.05 & p<0.001) in study group subjects, which clarify the role of lipid peroxidation in knee OA progression and development of CVD risk. Oxidation of lipids is well controlled by antioxidant enzymes including plasma paraoxonase, an enzyme found in association with HDL contributing it to anti-atherogenic and antioxidant capability by hydrolyzing specific oxidized phospholipids and cholesterol linoleate hydroperoxides, and by neutralizing hydrogen peroxide.…”
Section: Discussionsupporting
confidence: 65%
“…The incidence of OA increases during every decade of life, and by the age of 65 years, most of the elderly has OA of knee joints. 1 Its prominent feature is the progressive destruction of articular cartilage which results in impaired joint motion, severe pain, structural and functional failure of synovial joints. 2 Consequently, the patients become physically inactive.…”
mentioning
confidence: 99%
“…The hypothesis that this imbalance in signaling may result from the excessive levels of ROS that have been observed in OA cartilage (14,17,18) was supported by the findings that induction of oxidative stress in normal chondrocytes with tBHP reproduced the changes seen in OA cells, whereas treatment of OA cells with anti-oxidants improved the balance of Akt to ERK phosphorylation and improved the anabolic response of the cells to IGF-I.…”
Section: Discussionmentioning
confidence: 94%
“…Oxidative Stress Inhibits IGF-I-mediated IRS-1-Akt Signaling but Activates MEK-ERK-We hypothesized that increased levels of endogenous ROS due to oxidative stress, previously shown to be present in OA cells (11,14,17,18), might act to inhibit IGF-I signaling. To test this, we induced oxidative stress in normal human chondrocytes by incubating cultures for 30 min with 250 M tBHP.…”
Section: Oa Chondrocytes Possess a High Basal Level Of Irs-1 Serine Amentioning
confidence: 99%
“…Lipid peroxides could behave as secondary toxic trigger causing further damage by modulating membrane fluidity, permeability and transport, enhancing the risk of CVDs in arthritic patients [35]. Protein modification leads to malfunctioning of a variety of regulatory, structural and functional proteins like cell receptors, signal transducers and enzymes [36].…”
Section: Discussionmentioning
confidence: 99%